(untitled) (Asian Journal of Medical and Biological Research, 2016)
The study was conducted at Bhadrabila union, Narail sadar upazila, Narail in Bangladesh. The study period was carried out during September to December, 2013. In the selected areas, the study was conducted on 375 persons. The collected information was totally interview and observation based study. In the study area the highest age distribution was 50% in 21-40 years. The second highest was 39% for 41-60 years. The third highest was 7% for the year of 1-20. The lowest age distribution was for the year of 60 and above. This study found that the highest respondents of 39% are the member of 3-4 family member range. 32% respondents are in the member of 5-6 family member range. 12% respondents are in the member of 7-8 family member range. This study represent that 18% houses were kacha, 27% houses were tin shade 29% half building and 26% house were building. Almost 3% respondents were in class 1-3, 31% were in class 4-6, 46% were in between class 7-9, 10% in S.S.C level and left 9% were in above S.S.C level. Almost 79% had sanitary latrine. . It was found that 28% peoples were and poor their monthly income was 3,000-6,000 taka, 40% peoples were middle class their monthly income was 6,000-9,000 taka, about 24% peoples were rich their monthly income was 9,000-12,000 and lest 8% peoples income were 12,000+. 90% tube wells were arsenic free and only 10% tube wells are arsenic contaminated. About 77% were related with the BWDB and rests 13% were not the beneficiary of the BWDB. About 86% respondants were benifited by the activities of the BWDB. About 100% of respondents are fully satisfied by the activities of BWDB in arsenic test. It was shown that the social life of the respondents of Bhadrabila Union Parisad was getting better. The most important thing is almost 100% of the respondents were satisfied by the activities of BWDB. Asian J. Med. Biol. Res. June 2016, 2(2): 297-303